Design and Synthesis of azo Derivatives of 5-Fluorouacil for Targeting Colon Cancer - Ulaiwy, Mohammad Abdul Amir; Mohammed, Mohammed Hassan (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
Â Â 5-Fluorouracil (5-FU) is a drug that belong to the antimetabolite class of antineoplastic agents, with a broad spectrum of activity against solid tumors, the use of oral 5-FU was abandoned decades ago because of its irregular absorption and rapid degradation. A potential strategy to improve the selective properties of 5-FU is the chemical transformation into reversible derivatives (prodrugs) which are converted to the parent drug by virtue of enzymatic or chemical means. In the present study, three derivatives of 5-fluorouracil have been designed to be synthesized as an azo derivatives of 5-fluorouracil in order to selectively deliver 5-fluorouracil into the cancer cells of the colon. The synthesis of the target compounds were accomplished following multistep reaction procedures. The chemical reactions were followed up and purity of the products was checked by TLC. The structure of the final compounds and their intermediates were characterized and identified by their melting points, infrared spectroscopy and elemental microanalysis. Compounds 2 and 3 were subjected to a stability study in phosphate buffer (pH 1.5 and 7.8) for different time intervals (0 â€“ 240 min) at 37Â°C.